Value Added Implementasi Enterprise Resource Planning (ERP) - Widaninggar, Nanda (Akmenika, 2013)
Management Information System became pivotal aspect since manager’s decision was made according to the information managed in the database. Enterprise Resource Planning (ERP) was not a brand new issue in Information and Communication Technology (ICT), but the development of this system never got stop. The aim of the implementation of ERP, initially, assisted the operational process of the company, moreover, in PT. Bentoel Internasional Investama Tbk.--a tobacco company which had so many barriers in its industries-- ERP added the value of the company in a very large aspects by using its Be-One. The used of ERP concept increased the productivity and customer satisfaction in the past nine years, and it brought PT. Bentoel Internasional Investama Tbk. to be the best e-Corporation in Indonesia according to SWA magazine version in 2010. ICT through the ERP, did not only create the automation process and efficiency, but also created the improvement of performance and finally changed the stakeholder’s paradigm into customer-centric.